Modelling the influence of sustainable leadership on the performance of construction firms using structural equation modeling approach - Otali, Monday; Achuenu, Emmanuel; Ujene, Anthony (Penerbit Universiti Kebangsaan Malaysia, 2021)
The quest for sustainability of construction firms demands that the firms should have leaders who will drive and implement the sustainability agenda at the firm level for improved firm performance. The aim of the study was to establish the influence of sustainable leadership on the performance of construction firms using a structural equation modeling approach. In tandem with the survey approach adopted for the study, 1179 copies of the structured questionnaires were administered while 980 valid responses were received giving a response rate of 83.2%. Data were analyzed using descriptive statistics and structural equation modeling. The model estimation and modification, verification, and validation were carried out. The results revealed that sustainable leadership positively influences the performance of construction firms (β= 0.83). The study showed that sustainable leadership accounts for 68.3 % of the variability in the overall performance of construction firms. Specifically, this study revealed that sustainable leadership accounts for 60.9%, 56.2%, 36%, 85.6%, and 68.6% of the variability in remuneration and benefit of employees, employees relationship, the general employees satisfaction, social performance, and environmental performance of the firm respectively This study concludes that the extent of implementation of sustainable leadership principles among construction firms positively influenced the performance of construction firms.